2011
DOI: 10.1093/eurheartj/ehq406
|View full text |Cite
|
Sign up to set email alerts
|

Standardized endpoint definitions for transcatheter aortic valve implantation clinical trials: a consensus report from the Valve Academic Research Consortium

Abstract: ObjectivesTo propose standardized consensus definitions for important clinical endpoints in transcatheter aortic valve implantation (TAVI), investigations in an effort to improve the quality of clinical research and to enable meaningful comparisons between clinical trials. To make these consensus definitions accessible to all stakeholders in TAVI clinical research through a peer reviewed publication, on behalf of the public health.BackgroundTranscatheter aortic valve implantation may provide a worthwhile less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
654
2
14

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 915 publications
(681 citation statements)
references
References 161 publications
11
654
2
14
Order By: Relevance
“…Death, stroke, myocardial infarction, and reintervention were adjudicated by an independent Clinical Events Committee consisting of TAVI-experienced interventional cardiologists and a cardiac surgeon using the initial Valve Academic Research Consortium definitions. 9 An independent neurologist reviewed the neurological events and provided a summary of each event to the Clinical Events Committee, which used this information along with any other patient source data to adjudicate all neurological events. A core laboratory Comparisons between anesthesia types are based on chi-square or Fisher's exact tests for categorical variables, and t-tests or Wilcoxon tests for continuous variables, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Death, stroke, myocardial infarction, and reintervention were adjudicated by an independent Clinical Events Committee consisting of TAVI-experienced interventional cardiologists and a cardiac surgeon using the initial Valve Academic Research Consortium definitions. 9 An independent neurologist reviewed the neurological events and provided a summary of each event to the Clinical Events Committee, which used this information along with any other patient source data to adjudicate all neurological events. A core laboratory Comparisons between anesthesia types are based on chi-square or Fisher's exact tests for categorical variables, and t-tests or Wilcoxon tests for continuous variables, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…The devices used int hi sst ud yan dth eT A V Rp r o c e d ur eh av ebe e np r eviously described (12)(13)(14).T h eb a l l o o n -e x p a n d a b l e valve used in this trial (Edwards SAPIEN XT; Edwards Lifesciences, Irvine, California) is a cylindrical cobalt-chromium stent into which 3 leaflets made of bovine pericardium are mounted, whereas the self- STUDY ENDPOINTS. The pre-specified primary endpoint of the CHOICE trial was "device success," as defined by the first Valve Academic Research Consortium (VARC) consensus document (15) and has been previously reported (12).A l lp a t i e n t sw e r e followed-up for at least 1 year and had clinical visits and echocardiographic evaluations at 6 months and 1 year. Pre-specified secondary endpoints included cardiovascular mortality, stroke, repeat hospitalization for heart failure, NewY o r kH e a r tA s STATISTICAL ANALYSIS.…”
Section: Methodsmentioning
confidence: 99%
“…12,13) The aim of our study was to assess the incidence and predictors of VARC-2 bleeding complications in patients undergoing TAVI and to determine their impact on mid-term prognosis.…”
Section: )mentioning
confidence: 99%
“…11) To address the issue of heterogeneous reporting of outcomes in patients undergoing TAVI, in 2011 the Valve Academic Research Consortium (VARC) developed a set of unified criteria for standardized definition of clinical endpoints, which were recently updated and published as VARC-2. 12,13) The aim of our study was to assess the incidence and predictors of VARC-2 bleeding complications in patients undergoing TAVI and to determine their impact on mid-term prognosis.…”
mentioning
confidence: 99%